Contents of conjugated linoleic acid isomers in ruminant-derived foods and estimation of their contribution to daily intake in Portugal - Martins, Susana V. (2015)
The present study provides a detailed overview of the contents of conjugated linoleic acid (CLA) isomers in the most consumed Portuguese CLA-rich foods (milk, butter, yoghurt, cheese, beef and lamb meat), by using silver ion-HPLC. In addition, the contribution of these ruminant-derived foods to the daily intake of CLA isomers was estimated based on Portuguese consumption habits. The total CLA concentration in milk and dairy products ranged from 4.00 mg/g fat in yoghurt to 7.22 mg/g fat in butter, and, regarding meats, from 4-45 mg/g fat in intensively produced beef to 11.29 mg/g fat in lamb meat. The predominant CLA isomers identified in these products were cis-9,trans-11 (59.89-79.21 %) and trans-7,cis-9 (8.04-20.20%). The average estimated total CLA intake for the Portuguese population was 73.70mg/d. Milk and cheese are probably the two products with the highest contribution to the final CLA intake, as a result of their high fat content and consumption values. The results also suggested that cis-9,trans-11 and trans-7,cis-9 are the isomers most represented, with, respectively, 76.10 and 12.56 % of the total CLA intake. Being the first detailed report on the contents of total and individual CLA isomers in Portuguese commercial ruminant-derived foods, we further discuss the implication of the results for diet characteristics and human health.